OR FORUM—The Evolution of Closed-Loop Supply Chain Research - Guide, V. Daniel R.; Van Wassenhove, Luk N. (Operations Research, 2009)
The purpose of this paper is to introduce the reader to the field of closed-loop supply chains with a strong business perspective, i.e., we focus on profitable value recovery from returned products. It recounts the evolution of research in this growing area over the past 15 years, during which it developed from a narrow, technically focused niche area to a fully recognized subfield of supply chain management. We use five phases to paint an encompassing view of this evolutionary process for the reader to understand past achievements and potential future operations research opportunities.